Nutritional facts concerning goat milk (Capra hircus) and its variations during the agroindustrial process. - Chacón Villalobos, Alejandro (2005)
This paper overviews the main nutritional aspects of goat milk,such as chemical composition (protein, amino acids,minerals, bioactive factors and fat), nutritional value,functional value, hypoallergenic properties, and the effects ofagroindustrial processing (refrigeration, freezing, and heattreatment).